2016
DOI: 10.4102/curationis.v39i1.1571
|View full text |Cite
|
Sign up to set email alerts
|

Social factors determining maternal and neonatal mortality in South Africa: A qualitative study

Abstract: BackgroundSouth Africa’s maternal mortality ratio has increased from 150/100 000 in 1990 to 269/100 000 live births in 2015 against the Millennium Development Goals 5 (MDG5) target of 38/100 000, indicating slow progress in improving maternal health. The neonatal mortality rate was 14/1000 live births against the MDG4 target of 7/1000. The purpose of the article was to outline the socio-economic factors that determine maternal and neonatal mortality in South African communities.ObjectivesTo identify and descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…With 68% of the population living on less than $1.25 per day and 86.9 million of its 180 million inhabitants living in extreme poverty [3132], the high level of perinatal mortality in Nigeria could be a result of poverty in the country. Poverty remains an underlying factor associated with poor birth outcomes, and studies have shown a significant association between poverty and perinatal mortality [3334]. Poverty is multidimensional, with economic, political, social, governance, health and environmental components that influence child survival at the individual, household and societal level [3536].…”
Section: Discussionmentioning
confidence: 99%
“…With 68% of the population living on less than $1.25 per day and 86.9 million of its 180 million inhabitants living in extreme poverty [3132], the high level of perinatal mortality in Nigeria could be a result of poverty in the country. Poverty remains an underlying factor associated with poor birth outcomes, and studies have shown a significant association between poverty and perinatal mortality [3334]. Poverty is multidimensional, with economic, political, social, governance, health and environmental components that influence child survival at the individual, household and societal level [3536].…”
Section: Discussionmentioning
confidence: 99%
“…Mistreatment and disrespect reports to women during the parturition process in health institutions are not recent, although their elimination is a claim of social movements for human rights, which in recent years have gained visibility because of the scientific evidence on the low quality impact of care during the pregnancy-puerperal period for women and children (1)(2) . These events have promoted conceptual advances on violence in institutionalized childbirth in the legal, political, and welfare practices, shaking government agendas (3)(4) .…”
Section: Introductionmentioning
confidence: 99%
“…Other barriers operate to reduce supply, affordability and availability of these services. These include out-of-pocket health expenditures [33], inattention to reproductive health and rights [37], poor quality of health care [37], inadequate staffing [38], and lack of training of health providers [36], fear of being neglected or maltreated by health workers [34,36]. Our study adds onto existing literature showing that women who inject drugs may particularly be affected by these barriers [23,26,39].…”
Section: Discussionmentioning
confidence: 85%